2005
DOI: 10.1111/j.1471-4159.2005.03072.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of EFA6C, a third member of the EFA6 family, in adult mouse Purkinje cells

Abstract: EFA6C is a third member of the EFA6 family of guanine nucleotide exchange factors (GEFs) for ADP-ribosylation factor 6 (ARF6). In this study, we first demonstrated that EFA6C indeed activated ARF6 more selectively than ARF1 by ARF pull-down assay. In situ hybridization histochemistry revealed that EFA6C mRNA was expressed predominantly in mature Purkinje cells and the epithelial cells of the choroid plexus in contrast to the ubiquitous expression of ARF6 mRNA throughout the brain. EFA6C mRNA was already detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 46 publications
(104 reference statements)
2
42
1
Order By: Relevance
“…Northern blot results indicate that EFA6C is mainly expressed in brain, similar to EFA6A, whereas EFA6B shows a widespread tissue distribution (Derrien et al, 2002). EFA6C is detected in spines at the electron microscopic level and enriched in PSD fractions (Matsuya et al, 2005). Our results (Fig.…”
Section: Role Of Efa6a In Spine Development and Maintenancesupporting
confidence: 74%
See 1 more Smart Citation
“…Northern blot results indicate that EFA6C is mainly expressed in brain, similar to EFA6A, whereas EFA6B shows a widespread tissue distribution (Derrien et al, 2002). EFA6C is detected in spines at the electron microscopic level and enriched in PSD fractions (Matsuya et al, 2005). Our results (Fig.…”
Section: Role Of Efa6a In Spine Development and Maintenancesupporting
confidence: 74%
“…Our results (Fig. 1 B) and previous reports indicate that EFA6C is highly expressed in cerebellar Purkinje cells (Matsuya et al, 2005), in contrast to the preferential expression of EFA6A in forebrain areas (Suzuki et al, 2002) and widespread expression of ARF6 (Suzuki et al, 2001), suggesting that EFA6 family isoforms may differentially interact with ARF6 in brain regions. In addition to EFA6 family proteins, brain expresses other families of ARF GEFs, including ARF GEP 100 (ARF6 specific) (Someya et al, 2001) and ARNO/GRP/cytohesin (ARF1 and ARF6 specific) (Nie et al, 2003).…”
Section: Role Of Efa6a In Spine Development and Maintenancecontrasting
confidence: 54%
“…It remains to be elucidated whether a smaller EFA6A polypeptide is an alternatively spliced form or artifact. Subsequent cDNA analyses revealed that the EFA6 family consists of four members (EFA6A, EFA6B, EFA6C, and EFA6D) (Derrien et al 2002;Matsuya et al 2005;Sakagami et al 2006). The overall domain organization is conserved among the EFA6 family in that it comprises a variable N-terminal region, a central catalytic Sec7 domain, a pleckstrin homology (PH) domain and a C-terminal coiled coil motif (Fig.…”
Section: Structurementioning
confidence: 99%
“…A recent phylogenic analysis of Sec 7 domains has proposed to classify 15 mammalian ARF-GEFs into six families (Cox et al 2004): the brefeldin A-inhibited GEF (BIG)/ Sec7 family, Golgi-specifi c brefeldin A-resistance factor (GBF)/GEA family, EFA6 family, cytohesin family, brefeldin A-resistant ARF-GEF (BRAG) family and F-box only protein 8 (FBX8). Among these, ARF-GEFs that can activate ARF6 are four members in the EFA6 family (EFA6A, EFA6B, EFA6C and EFA6D) (Franco et al 1999;Derrien et al 2002;Matsuya et al 2005;Sakagami et al 2006), ARF nucleotide binding site opener (ARNO)/cytohesin-2 (Frank et al 1998) and GRP-1/ARNO-3/cytohesin-3 (Langille et al 1999) in the cytohesin family, and ARF-GEP10 in the BRAG family (Someya et al 2001). We have studied with a special attention to the EFA6 family, because of the following attractive reasons: (1) The EFA6 family is the fi rst ARF-GEF identifi ed to be specifi c for ARF6 (Franco et al 1999).…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation